Good Governance Combination of Local Governance and E-Governance: A Conceptual Framework (Indian Journal of Management and Language (IJML), 2024)
Our nation has the longest written constitution but the implementation of the Local Governance has been transferred and their efficiency has properly monitored or rectified by the state and central government. This is conceptual research has been done in the implementation process. This research mainly focused on quality of life. The Lack of Implementation process is connected with resource exploitation. Resource exploitation has two type’s human resource exploitation and natural resource exploitation. The directly three systems are connected with sustainable development but overall development left without because of bureaucratic, social leaders, and Knowledgeable people this research is not critical research but this research has a starting point for many reformations. This concept has defined implementation process is not based on rule of law it should be considered by social issues and clearly instructing for the proper implementation process and reduce the level exploitation and monitoring the unethical professionals and their rectification processing time will be less. This concept has separated no proper implementation process and improper implementation and analyzing the important factors for the proper implementation process. The factors like misuse of power and inefficiency should not affect the proper implementation process. The result of the lack of implementation process is organized resource exploitation. This plan will reduce the worst handling of decentralization process may be a strong reason for the lack of implementation process will directly connect with the organized resource exploitation. This research focusing on the efficiency and equity of the governance strongly insisted people should train by the local governance free from favoritism, partial’s and nepotism, thisplanhas look into transforming the local governance. It will solve prolonging and procrastination in their issues It will reduce the organized crime result of lack of implementation process. Identify the exploiter or victim. The idea will combine the education system Social system and governance syste into one roof. To analyze all type of social issues and protect the weaker section.